Willms’ Tumor Propaated to the Inferior Vena Cava - Cepellini, Raúl; Torres, Daniel; Arruti, César; Wettstein, Juana M; Chavarría, Oscar; Ravera de Bengochea, Dora; Falconi, Luis; Anavitarte, Eduardo (Cirugía del Uruguay, 1981)
A 2 - years old girl with a large nephroblastoma of the rigth kidney with involvement of the inferior vena éava. Radical Excision including cavotomy, and associated chemotherapy and radiotherapy resulted in a 22 months postoperative disease - free survival'.